Efficient Synthesis of Diacetoxyiodoarenes via Intramolecular Rearrangement - Zhou, De-Jun; Zhai, Yang-Yang; Meng, Ling-Pu; Song, Wei-Wei; Liu, Xiao; Yin, Shu-Qiang (Letters in Organic Chemistry, 2019)
This study introduces a concise and efficient method for preparing diacetoxyiodoarenes from the corresponding iodoarenes. In the presence of acetic anhydride, iodoarenes were oxidized to diacetoxyiodoarenes by sodium perborate in acetic acid under argon protection at 55°C in ideal yields. Through this method, 10 diacetoxyiodoarenes were obtained smoothly.
Keywords: intramolecular rearrangement